The surprising duality of Jugaad : low firm growth and high inclusive growth - Shepherd, Dean A.; Parida, Vinit; Wincent, Joakim (Wiley, 2019)
Western theories on creativity emphasize the importance of access to resources andthe generation of innovations as a source of sustainable competitive advantage for firms.However, perhaps the emphasis on slack resources and the firm as the level of analysis maybe less appropriate for understanding the benefits of individual creative problem solving inresource-poor environments of the east; focusing solely on the firm is not sufficiently inclusiveand may underestimate the benefits of creative problem solving under resource scarcity.Through an inductive interpretive case study of 12 problem solvers in the highly resource-poor environment of rural India, we identified the antecedents, dimensions and duality ofoutcomes for an Indian cultural source of creative problem solving called jugaad. Jugaadrelies on assertive defiance, trial-and-error experiential learning and the recombination ofavailable resources to improvise a frugal quick-fix solution. Our inductive framework providesnew insights into the dual outcomes of creative problem solving from an eastern perspective;jugaad is unlikely to be a source of competitive advantage for firm growth but represents asource of enhanced wellbeing for inclusive growth.
Keywords: creativity; inclusive growth; innovation; social entrepreneurship; fi=Johtaminen ja organisaatiot|en=Management and Organization|